2010
DOI: 10.1371/journal.pone.0015051
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of HIV-1 Viral Load Monitoring of Patients Initially Successfully Treated with Combination Antiretroviral Therapy

Abstract: BackgroundAlthough considered an essential tool for monitoring the effect of combination antiretroviral treatment (CART), HIV-1 RNA (viral load, VL) testing is greatly influenced by cost and availability of resources.ObjectivesTo examine whether HIV infected patients who were initially successfully treated with CART have less frequent monitoring of VL over time and whether CART failure and other HIV-disease and sociodemographic characteristics are associated with less frequent VL testing.MethodsThe study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…For example, in 2009, out of 26 antiretroviral drugs registered in the EU, only 14 were available in Croatia. 5 The majority of HIV-1 infections in Croatia are associated with subtype B. Molecular analysis of HIV subtypes in 145 Croatian patients (2001)(2002)(2003) from different risk groups showed that 26% of infections were due to non-B subtypes (predominantly CRF02_AG, subtype C, subtype A, and CRF10_CD). 6 Non-B subtype infections were found only in Croatian patients with heterosexual exposure (predominantly seafarers and their steady female partners) whereas HIV epidemics in MSM were due to subtype B infections only.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in 2009, out of 26 antiretroviral drugs registered in the EU, only 14 were available in Croatia. 5 The majority of HIV-1 infections in Croatia are associated with subtype B. Molecular analysis of HIV subtypes in 145 Croatian patients (2001)(2002)(2003) from different risk groups showed that 26% of infections were due to non-B subtypes (predominantly CRF02_AG, subtype C, subtype A, and CRF10_CD). 6 Non-B subtype infections were found only in Croatian patients with heterosexual exposure (predominantly seafarers and their steady female partners) whereas HIV epidemics in MSM were due to subtype B infections only.…”
Section: Introductionmentioning
confidence: 99%
“…Persons in our study with a CD4 cell count < 200 cells/mm 3 were more likely to have virologic failure at 12 months. CD4 cell count at entry into our cohort may be at least a partial surrogate for duration of viral suppression prior to entering the cohort (a variable that we could not measure).…”
Section: Follow-up Intervals and Virologic Failurementioning
confidence: 64%
“…Similar numbers of participants had private health insurance, Medicare, Medicaid, and no insurance. The median (IQR) CD4 cell count at the index visit was 497 (345, 692) cells/mm 3 . Sixty-six percent of participants had a followup appointment scheduled at 3 months, 26% at 4 months, and 8% at 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are similar to data reported by Romih and colleagues in Croatia involving a smaller cohort of 128 patients initiating cART, in which there was no difference in VL monitoring frequency between patients who did or did not experience VF. 7 Another small randomized prospective study found no difference in VF rates among 165 individuals with CD4 ≥250 cells/mm 3 and undetectable VLs for more than 12 months who were randomized to receive VL monitoring either every 4 or every 6 months. 8 …”
Section: Resultsmentioning
confidence: 99%